(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The development of the polymerase chain reaction method by Carrie Mullis in 1983 can be considered a new era of laboratory diagnostics (in particular, tuberculosis diagnostics). PCR makes it possible to detect the deoxyribonucleic acid of the pathogenic agent regardless of its quantitative content in the biological media of the organism. Many domestic and foreign works [3,4,5,6,7] testify to the high efficiency of this method both in adults and in children and adolescents.